GREEN HRD : SEBUAH LITERATURE REVIEW TENTANG DAMPAK DAN IMPLIKASINYA MENUJU ORGANISASI YANG BERKELANJUTAN - Marini Marini; Ary Dwi Jatmiko; Andini Dwi Arumsari (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: Climate change and sustainability challenges compel organizations to incorporate sustainable environmental principles into their operational framework. Green Human Resource Development (Green HRD) is a strategic paradigm that emphasizes training, developing, and empowering personnel to advocate for sustainability initiatives. Objective: This scholarly article provides a comprehensive review of the extant literature related to Green HRD, covering its determinants, key components, and impacts on organizational performance. Result: Green HRD plays a critical role in driving economic prosperity, enhancing social welfare, and promoting environmental sustainability. Internal determinants such as organizational culture and leadership dynamics, alongside external influences including government regulations and advances in green technologies, are critical to the effective implementation of Green HRD. In addition, critical components such as sustainability-focused training, green career development pathways, and employee engagement initiatives yield beneficial effects on operational efficiency, organizational reputation, and environmentally driven innovation. Conclution: Empirical evidence is lacking in assessing the long-term effects and practical application of Green HRD in specific sectors, especially in the context of developing countries. Future research efforts are recommended to concentrate on success metrics, green technology integration, and cross- cultural methodologies to enhance the efficacy of Green HRD in facilitating global sustainability initiatives.